NEW APPROACH IN URTICARIA TREATMENT - A. V. Samtsov (State Scientific Center of Dermatovenereology and Cosmetology, 2017)
The article presents the European Guidelines for the Diagnostics and Management of Urticaria (revised in 2013) and new data on the physiopathology of urticaria related to the role of the platelet-activating factor (PAF) activating mast cells, attracting eosinophils and neutrophils, improving vascular permeability (it is more potent than histamine by 1,000 times) and mucosal edema, and increasing the level of pro-inflammatory cytokines. The data promoted the creation of a new rupatadine molecule, which blocks histamine and PAF receptors at the same time improving the therapeutic effect during urticaria treatment as compared to other antihistamine drugs. The author presents the study results confirming the efficacy and safety of rupatadine.